Biotechnological production of biogrout from iron ore and cellulose - Stabnikov, Viktor (2018)
BACKGROUND Grouts are used in construction, agriculture, aquaculture, and environmental engineering to reduce the hydraulic conductivity of soil. Known chemical grouts could be replaced in some cases by new biogrouts, which are based on microbially‐induced precipitation of minerals. The aim of the present paper was to study the production and properties of iron‐based biogrout. RESULTS Iron‐based biogrout was produced from hematite iron ore and cellulose by associations of iron‐reducing and cellulose‐fermenting bacteria selected from the bottom sediments of the Dead Sea and mangrove swamp. The concentration of dissolved ferrous ions produced was proportional to the quantity (surface) of the iron ore particles. Precipitation of ferric hydroxide in the pores of sand was supported by urease‐producing bacteria. The hydraulic conductivity of sand after treatment with the iron‐based biogrout decreased from 7 × 10−4 m s−1 to 1.4 × 10−6 m s−1 with 4.5% (w/w) content of iron in biocemented sand. CONCLUSIONS Low cost iron‐based biogrout can be produced using anaerobic fermentation of cellulose and bioreduction of hematite iron ore. Bio‐induced precipitation of ferric hydroxide could be used in practice for the sealing of agricultural channels, aquaculture and wastewater treatment ponds, landfill sites, dams and retaining walls, and the tunneling space before or after excavation.